The role of frontal thrusts in tsunami earthquake generation - Felix, Raquel P. (2023)
The frontal sections of subduction zones are the source of a poorly understood hazard: “tsunami earthquakes,” which generate larger-than-expected tsunamis given their seismic shaking. Slip on frontal thrusts is considered to be the cause of increased wave heights in these earthquakes, but the impact of this mechanism has thus far not been quantified. Here, we explore how frontal thrust slip can contribute to tsunami wave generation by modeling the resulting seafloor deformation using fault-bend folding theory. We then quantify wave heights in 2D and expected tsunami energies in 3D for both thrust splays (using fault-bend folding) and down-dip décollement ruptures (modeled as elastic). We present an analytical solution for the damping effect of the water column and show that, because the narrow band of seafloor uplift produced by frontal thrust slip is damped, initial tsunami heights and resulting energies are relatively low. Although the geometry of the thrust can modify seafloor deformation, water damping reduces these differences; tsunami energy is generally insensitive to thrust ramp parameters, such as fault dip, geological evolution, sedimentation, and erosion. Tsunami energy depends primarily on three features: Décollement depth below the seafloor, water depth, and coseismic slip. Because frontal ruptures of subduction zones include slip on both the frontal thrust and the downdip décollement, we compare their tsunami energies. We find that thrust ramps generate significantly lower energies than the paired slip on the décollement. Using a case study of the 25 October 2010Mw 7.8 Mentawai tsunami earthquake, we show that although slip on the décollement and frontal thrust together can generate the required tsunami energy, <10% was contributed by the frontal thrust. Overall, our results demonstrate that the wider, lower amplitude uplift produced by décollement slip must play a dominant role in the tsunami generation process for tsunami earthquakes.